Konstantin Stanislavsky - Merlin, Bella (London, New York : Routledge, 2007)
Biography in Social and Artistic Context -- Summary and Analysis of An Actor Prepares -- Description and Analysis of The Seagull -- Practical Exercises.
boek
Keywords: Stanislavsky, Konstantin